Mass scale sugar-mediated green synthesis and DSSCs application of tin oxide nanostructured photoanode: Effect of zinc sulphide layering on charge collection efficiency - Shaikh, Shoyebmohamad F.; Mane, Rajaram S.; Joo, Oh-Shim (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
Table-top (market quality) sugar-mediated green synthesis of tin oxide (SnO2) spherical nanocrystallites (NCs) of 40-60 nm is reported, passivated with 2, 4 and 6 layers (L) of zinc sulphide (ZnS) and envisaged in dye sensitized solar cells (DSSCs). All photoanodes i.e. without and ZnS-passivated SnO2 (SnO2-ZnS NCs) are characterized for their structure, morphology, optoelectrochemical properties. SnO2-ZnS NC-electrodes show appreciable DSSCs performance due to an enhanced dye loading capability, light scattering ability, and suppressed recombination rate. The optimized SnO2-(4L) ZnS NC-photoanode demonstrates 200% enhancement in the power conversion efficiency compared to SnO2 NC-based photoanode. This is due to prolonged transient photovoltage decay and higher charge recombination resistance with a minimized recombination rate of photoelectrons. Mott-Schottkymeasurementsconfirm a negative shift in the conduction band position of SnO2-(4L) ZnS NCs photoanode (0.41 V) compared to SnO2 NC-photoanode.
Keywords: SENSITIZED SOLAR-CELLS; ZNO NANOWIRE ARRAYS; SNO2 THIN-FILMS; PHOTOVOLTAIC PERFORMANCE; NANOCRYSTALLINE TIO2; HIGHLY EFFICIENT; PHOTOLUMINESCENCE PROPERTIES; ELECTRON INJECTION; OPTICAL-PROPERTIES; TITANIUM-OXIDE